The position of the principals of the basic government schools from the adoption of the "Management Program in Values" is an entry point to limit the students' orientation to private lessons from their point of view (Journal of the College of Basic Education, 2022)
Abstract:A field study aimed at identifying the position of the principals of the basic government schools from the adoption of ((management program in values)) an approach to solve their students' approach to private lessons, adopted the descriptive analytical approach. The research community consisted of (179) Director and Director of Basic Government Schools in Education and Education in Jarash Governorate / Jordan . The sample was randomly selected by (78,212%) of the research community. The sample consisted of (140) managers.A questionnaire was developed consisting of (50) paragraphs divided between five areas. And its validity and stability were confirmed. The researchers used the SPSS program to analyze data obtained from the application of the questionnaire in the first semester of 2015-2016. And reached the following results: The position of principals of the principals management program to reduce the orientation of students for private lessons was positive and consistent with the adoption of the program at a high rate.Keywords: Director, Basic Schools, Management Program in Values, Tutoring.